Analisis Resepsi Ibu Rumah Tangga di KEC. Johar Baru mengenai Peran Gender dalam Sinetron Komplek Pengabdi Istri di RCTI - Andreas Cesar Silalahi; Heppy New Year Haloho (UNIVERSITAS KALBIS, 2022)
Gender issues in soap operas often make people feel interested in watching the soap opera. This study aims to determine the meaning of housewives kec. New johar in the soap opera Komplek Pengabdi Istri at RCTI by using three position categories, namely the position of dominant hegemony, negotiations and opposition. This study uses a qualitative approach to the type of descriptive research and encoding-decoding theory by Stuart Hall. Researchers analyzed using the Khalyak reception analysis method. The results showed that there were differences in meaning in each of the information described in the soap opera Komplek Pengabdi Istri regarding gender roles. The position on the meaning of negotiation and opposition to information about the role of the wife making a living, the exchange of successful roles and the role of the wife are more important. Dominant hegemony becomes a position of meaning that does not dominate in any information on the soap opera Komplek Pengabdi Istri.